ARDL-Based Investigation of the Relationship between Monetary Policy and Inflation Mitigation - Fatur, Hassan Ali Osman; Dawwas, Abdalla bin Mubarak; Abaker, Abdelgalal Osman Idris; Mohamed, Sami Elsir Ahmed (PT Mattawang Mediatama Solution, 2025)
This study aims to estimate the efficiency of monetary policy in reducing inflation rates in Sudan for the years 2000 - 2022. The data of the study were collected from the Central Bank of Sudan and the Central Bureau of Statistics. To estimate the relationship between the variables, the study used statistical methods and econometric tools, including co integration error correction, and the Augmented Dickey-Fuller test. According to the results, there is a cointegration connection between the variables, and the variables are first order integrated. It was concluded that the estimated model is significant, and therefore it can be used to forecast, and that inflation is inversely related to both the exchange rate and the cost of financing, while the inflation is directly related to both bank credit and the money supply. To control inflation and stabilize exchange rates, a contractionary monetary policy was recommended